Anisotropic magnetoresistance behaviors in the layered ferromagnetic Cr2Ge2Te6. (21st October 2019) - Liu, Wei; Wang, Yamei; Han, Yuyan; Tong, Wei; Fan, Jiyu; Pi, Li; Hao, Ning; Zhang, Lei; Zhang, Yuheng
Abstract: The ferromagnetic semi-conductive Cr2 Ge2 Te6 with van der Waals bonded layers is prominent for characteristics of easy exfoliation and tunablility, which make it a potential candidate for spintronic application. Although the magnetism has been investigated intensively, the transport property is rarely studied, which is very important for the realization of its application. In this work, the electronic transport of Cr2 Ge2 Te6 is investigated under external magnetic field with variable directions. The angle-dependent resistance shows absolute isotropic property in the ab -plane. However, it displays anisotropic characteristic when the magnetic field is rotated from the ab -plane to the c -axis. The resistance reaches the maximum when H // c while it is the minimum when H // ab . Moreover, the field-dependent resistance of Cr2 Ge2 Te6 shows a positive magnetoresistance ( MR ) effect when H // c but a negative one when H // ab . We suggest that the anisotropic MR behaviors of Cr2 Ge2 Te6 can be understood theoretically within the framework based on the exchange interaction between the carriers and local magnetic moments.